Niedziela w Brunnen po latach - Zieliński, Jan (Colloquia Litteraria, 2011)
The author compares two visions of Europe, seen from Switzerland: one by the English economist David Ricardo, who was here in 1822, the second one by Czesław Miłosz, visiting this country in 1953. Link between both is Ricardo’s future Polish translator, at the same time brother of Miłosz’s maternal grandfather. Miłosz’s essay is discussed in the frame of the idea of the „liberation of Eastern Europe”, launched by his editor, Jerzy Giedroyc, in the early fifties, and of Arthur Koestler’s call for an European Legion of Liberty. After comparison of the text of Sunday in Brunnen with the iconographic programme of the parochial church in Brunnen the author comes to the conclusion that Miłosz wrote a work of fiction rather than a documentary report on his visit in this small place in Switzerland. Brunnen can be seen as an exemplum.